Magnetic linear tool (MagTool) / Nur Amirah Damia binti Md Nasser and Hayroman bin Ahmad - Md Nasser, Nur Amirah Damia; Ahmad, Hayroman (2019)
Simpler and faster construction are now a must-trend within the development of construction field. The reason for this is that the faster a project completes without quality defects, the greater the firm become at the world's eye. This paper presents the innovation project proposal for Magnetic Linear Tool (MagTool). A study has been conducted to identify the problem and issue related to the measurement tools in precast panel and surveying work. The objectives of this study are to evaluate the current tools available in the market and to propose suitable measurement tools that is user friendly in the industrial needs. A quantitative method, a questionnaire survey will be provided and distribute to selected range of individual and industry personnel who are related to the construction field especially for those involve in the measurement and surveying work. Another qualitative method by using interview to related personnel in the measurement and surveying work. The interview is mainly focus towards experiences workers who have been working for several years. Some of the literature studies are from the researched article and journals, relevant researches. Based on the data, there are many problems regarding the arising of b uilding inspection and installation in measurement and surveying works. Expected outcome will benefit the construction and industrial sectors.